Системы фазовой синхронизации - Акимов В. Н. Владимир Николаевич; Белюстина Л. Н. Людмила Николаевна; Белых В. Н. Владимир Николаевич; Бурдазейко Б. П.; Шахгильдян В. В. Ваган Ваганович (Москва, Радио и связь, 1982)
Авт. указаны на обороте тит. л.